Coping strategies during the COVID-19 lockdown: A multicultural study on self-related risks - Corazza, Ornella (2022)
The current COVID-19 pandemic has been affecting the body im age of individuals as well as their practice of physical exercise and their consumption of image- and performance-enhancing drugs (IPEDs) in an attempt to boost their appearance.